Răspuns :
[tex](x - 3)(x + 3) = 12 - (x - 2)(x + 2)[/tex]
[tex] {x}^{2} - {3}^{2} = 12 - ( {x}^{2} - {2}^{2} )[/tex]
[tex] {x}^{2} - 9 = 12 - ( {x}^{2} - 4)[/tex]
[tex] {x}^{2} - 9 = 12 - {x}^{2} + 4[/tex]
[tex] {x}^{2} + {x}^{2} = 12 + 4 + 9[/tex]
[tex]2 {x}^{2} = 25[/tex]
[tex] {x}^{2} = \frac{25}{2} [/tex]
[tex]x = \pm \sqrt{ \frac{25}{2} } [/tex]
[tex]x = \pm \frac{ \sqrt{25} }{ \sqrt{2} } [/tex]
[tex]x = \pm \frac{5}{ \sqrt{2} } [/tex]
[tex]x = \pm \frac{5 \sqrt{2} }{2} [/tex]
[tex] {x}^{2} - {3}^{2} = 12 - ( {x}^{2} - {2}^{2} )[/tex]
[tex] {x}^{2} - 9 = 12 - ( {x}^{2} - 4)[/tex]
[tex] {x}^{2} - 9 = 12 - {x}^{2} + 4[/tex]
[tex] {x}^{2} + {x}^{2} = 12 + 4 + 9[/tex]
[tex]2 {x}^{2} = 25[/tex]
[tex] {x}^{2} = \frac{25}{2} [/tex]
[tex]x = \pm \sqrt{ \frac{25}{2} } [/tex]
[tex]x = \pm \frac{ \sqrt{25} }{ \sqrt{2} } [/tex]
[tex]x = \pm \frac{5}{ \sqrt{2} } [/tex]
[tex]x = \pm \frac{5 \sqrt{2} }{2} [/tex]
(X-3)(x+3)=12-(x-2)(x+2)
=> x² - 9 = 12 - (x² - 4)
x² - 9 = 12 - x² + 4
2x² = 12+4+9
2x² = 25
x= √(25/2) ⇒ x₁ = 5√2/2 si x₂ = - 5√2/2
=> x² - 9 = 12 - (x² - 4)
x² - 9 = 12 - x² + 4
2x² = 12+4+9
2x² = 25
x= √(25/2) ⇒ x₁ = 5√2/2 si x₂ = - 5√2/2